A role of water in the porosity evaluation of ground-rock media - Jacek Traple; Stanisław Rychlicki; Kazimierz Twardowski (Acta Montanistica Slovaca, 2006)
In the pape,r the porosity was systemized in reference to multiphase multicomponent ground-rock media. The following geological-physical elements were accounted for: the geometry, the pore size in particular, the presence of strongly and weakly physically bounded water related to the structure of the electrical double layer, the rest saturation with water as a wetting phase, and a nonwetting phase represented by water immiscible fluids, in typical conditions e.g. air in the ground aeration zone, fluids and hydrocarbon gases.